Determinasi Kepuasan Kerja dan Implikasinya terhadap Turnover Intention: Studi pada PT Hayati Pratama Mandiri Padang - Marta Widian Sari; Nada Novia Deswira; Andriya Risdwiyanto (Universitas Proklamasi 45, 2023)
This study aims to determine the effect of work environment and financial compensation on turnover intention which is mediated by job satisfaction at PT Hayati Pratama Mandiri Padang, West Sumatera. The method used in this research is quantitative-descriptive. This study uses primary data collected through a questionnaire instrument from 60 permanent employees of PT Hayati Pratama Mandiri Padang. Data analysis in this study used multiple linear regression techniques to find the effect of independent variables on the dependent and path analysis to examine the effect of intermediary variables. Data analysis in this study used the help of the Statistical Product and Service Solution (SPSS) version 21. The results of this study indicate that the work environment has a significant and positive effect on job satisfaction, while financial compensation has no significant effect on job satisfaction. The opposite result was also obtained, i.e. the work environment did not have a significant effect on turnover intention, while financial compensation had a significant effect on turnover intention. Furthermore, job satisfaction does not have a significant effect on turnover intention. This study also proves that work environment and financial compensation have a significant effect on job satisfaction simultaneously. In line with these results, the work environment, financial compensation, and job satisfaction have a significant effect on turnover intention simultaneously. This study also confirms that job satisfaction is able to mediate the effect of the work environment on turnover intention. However, job satisfaction is not able to mediate the effect of financial compensation on turnover intention.